Bacterial purulent meningitis in children: is there a light at the end of the tunnel? - A. A. Vilnits; N. V. Skripchenko; E. Yu. Gorelik; A. V. Astapova; K. V. Markova; E. S. Egorova (LLC "Diagnostics and Vaccines", 2021)
Bacterial purulent meningitis is a life-threatening disease characterized by high mortality and severe consequences in survivors. Despite the modern possibilities of medicine, the disease continues to be a heavy burden on health care, the economy and society everywhere.Aim. To draw the attention of doctors to the problems associated with modern features of epidemiology, the consequences and possibilities of preventing bacterial purulent meningitis, especially in children, who constitute the main risk group for the development of this pathology.Literature review of Russian and foreign publications on the problem under consideration presented.Vaccination is recognized as one of the main tools for reducing morbidity and mortality from meningitis. Prophylactic vaccinations against N. meningitidis, Str.pneumoniae, H. influenzae, along with strict adherence to anti-epidemic measures in hospitals providing care to newborns, can help reduce the incidence of purulent meningitis in children and improve outcomes if they develop.